USM DAAD SUMMER SCHOOL STRENGTHENS EXPERTISE IN ELECTROPHYSIOLOGY - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 16 June 2015 – The recently concluded USM DAAD (Deutscher Akademischer Austauschdienst German Academic Exchange Service) Summer School, jointly organised by Universiti Sains Malaysia (USM) School of Pharmaceutical Sciences and School of Medical Sciences hosted 7 visiting professors and specialists from Germany to disseminate their expertise in the area of electrophysiology at USM.